Human ochratoxicosis and nephropathy in Egypt: A preliminary study - Wafa, EW; Yahya, RS; Sobh, MA; Eraky, I; El-Baz, M; El-Gayar, HAM; Betbeder, AM; Creppy, EE (African Journal of Nephrology, 2016)
<p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">This preliminary study was designed todelineate the extent of the problem of ochratoxicosis and its relation to renal diseases mounting to endstage renal disease (ESRD) or urothelial tumors inEgypt. It comprised 71 patient with renal diseases ofdifferent presentations. They were divided into fivegroups: (group I - no.=11) patients with (ESRD)under conservati ve treatment, (group 2 - no.=15)ESRD on regular hemodialysis, (group3 - no.= 15)renal allograft recipients, (group 4 - no.=15) patientswith nephrotic syndrome and (group 5 - no.=15)patients with urothelial tumors. In addition, twocontrol groups were included; potential relateddonors for renal transplantation (group 6 - no.=15)and healthy controls with negative family history ofrenal disease (group 7 - no.=25). <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">All groups were subjected to clinical, laboratory,radiological and histopathological evaluation of renalstatus together with determination of ochratoxin Alevel in blood, urine and in biopsy specimens ofpatients with urothelial tumors.High ochratoxin blood levels were found in allpatients with ESRD (groups 1 & 2) (p<0.01). Higherblood levels were detected in the group onconservative treatment (group 1) in comparison tocontrols possibly due to ochratoxin A clearance bydialysis. Ochratoxin A was detected in blood andurine of renal transplant recipients (group3) (p<0.01)and especially higher levels were found in patientswith nephrotic syndrome (group 4) (p<0.001). Patients with urothelial tumor (group 5), had higher levels of ochratoxin in blood, urine and tissue biopsy specimens (p<0.01). <p style="margin: 4px; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">These results support the conclusion that ochratoxin-A could be related to the genesis of renal disease leading to ESRD or causing urothelial cancer. We recommend more detailed study for ochratoxicosis & renal disease in Egypt.